Pelatihan Pengoptimalan Digital Marketing di Desa Nangsri Kebakkramat - Ilham Karin Rizkiawan; Nurul Aisah; Fahman Hadi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
MSMEs are very important for Indonesia because almost 60% of GDP is dominated by this sector. But in the process of running MSMEs in Nangsri Kebakkramat village, there are still don't understand how to promote appropriately according to the type of product being marketed, starting from increasing production costs, distribution systems, and most importantly, the lack of consumer knowledge about the products being sold.. This service aims to provide knowledge and training in creating advertising content and maximizing the use of promotional media. The method used the counseling method for an initial introduction to creating advertising content. Apart from providing material, the PKM team also provides practical methods or training on how to create advertising content and digital product marketing. It is hoped that MSME can carry out this service while running their businesses.using information technology to market products to a wider market online and offline.